Análise da prevenção de acidentes de trabalho no laboratório de química da UFERSA – Campus Caraúbas/RN - Gonçalves, Caio Wendel de Araújo (Universidade Federal Rural do Semi-Árido, 2018)
The chemistry laboratory is a widely used working environment inside universities, in which it has a framework of equipment, chemical agents, materials of various types, which are used, handled constantly. In this context, it can be said that laboratories are an environment conducive to the occurrence of occupational accidents, in which they can occur in various forms, such as short-circuits, intoxications and fires. Thus, the study of the prevention of work accidents in this type of place is of great importance, due to the risks experienced by the professionals who work there. In order to expand the studies of this nature, an analysis was performed in the laboratory environment of the UFERSA - Campus Caraúbas Chemistry Laboratory, observing its adequacy regarding the compliance with the norms required by the institution and the specific legislation for this work environment, besides complementary norms that are applied to prevent accidents. During the study, both the behavior of the professionals who used the laboratory daily and the application of the standards were analyzed, and compliance was observed to a great extent, but at other points, what was desired was not observed. Such failures can be cited in the question of the expiration of some Individual protection equipment, poor conservation of some equipment, an inappropriate place to store chemical reagents. In this sense there are parameters that need to be corrected for the well-being of all. Keywords:
Monografia
Keywords: Riscos de acidentes; Segurança do Trabalho; Normas Regulamentadoras; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA